2020
DOI: 10.1021/acs.jpclett.0c03195
|View full text |Cite
|
Sign up to set email alerts
|

Gas Phase Bond Formation in Dipeptide Clusters

Abstract: Protein bonds between amino acids are one of the most important biological linkages that create life. The detection of amino acids in the interstellar environments and in meteorites may lead to the suggestion that amino acids came from outer space and that peptides bonds may have been created in the gas phase. Here we show experimentally the creation of covalent bonds, most likely peptide bonds, between serine dipeptides in the gas phase. More specifically, we show that spraying a solution of Ser-Ser dipeptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 23 publications
2
10
0
Order By: Relevance
“…Closer inspection of the mass spectra also reveals the existence of protonated ions containing polyglycine with up to tetramers, i.e., H + Gly m=up to 4 . The results on serine dipeptide clusters 17 showed similar patterns in the mass spectrum obtained by MS/ MS of the H + Ser 2 (Ser) 3 cluster ion.…”
Section: ■ Results and Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Closer inspection of the mass spectra also reveals the existence of protonated ions containing polyglycine with up to tetramers, i.e., H + Gly m=up to 4 . The results on serine dipeptide clusters 17 showed similar patterns in the mass spectrum obtained by MS/ MS of the H + Ser 2 (Ser) 3 cluster ion.…”
Section: ■ Results and Discussionsupporting
confidence: 65%
“…In their recent work, Drozdovskaya et al reported a linear correlation between the abundances of different molecules relative to methanol observed with ALMA in IRAS 16293-2422 B (hot corinos) and also in comet 67P/ChuryumovGerasimenko with ROSINA, indicating that the presence of glycine in IRAS 16293-2422 B (hot corinos) could possibly be accessed by current spectroscopic techniques. In laboratory experiments, protonated polypeptide formation has previously been observed for other amino acids, including β-alanine, tryptophan, and serine . Furthermore, Nihamkin et al concluded that, provided the serine dipeptide can be generated abiotically, the polymerization process could occur readily.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…53−60 Peptide bond formation in the gas phase is attracting more and more interest. Indeed, it has been recently investigated in the collision-induced dissociation (CID) of (i) molecular clusters formed by tryptophan or serine molecules inside charged helium droplets 61 and (ii) protonated serine−serine dipeptides 62 as well as in the interaction of energetic highly charged ions with neural clusters of β-alanine. 32 In this work, we demonstrate that the VUV ionization of simple DKP molecules triggers a complementary route, with the formation of 5oxazolidinone and reactive species (71 and 71 + ) as prebiotic building blocks.…”
mentioning
confidence: 99%
“…Indeed, there are very little evidence of ICBF following LE‐CID. These include observations of PBF following LE‐CID of several protonated amino acids dimers [19] and a recent study of PBF in clusters of protonated serine dipeptides [20] . In both works PBF was not observed in protonated serine clusters following LE‐CID.…”
Section: Figurementioning
confidence: 94%